Polio eradication in Ghana: past, present, and future - Odoom, John Kofi; Laryea, Dennis Odai; Ntim, Nana Afia Asante; Attiku, Keren; Adjabeng, Michael; Duker, Ewurabena Oduma; Antwi, Comfort Nuamah; Gberbi, Emmanuel; Baffoe-Nyarko, Isaac; Adams, Patience Lartekai; Dickson, Angelina Evelyn; Boakye, Jessica Dufie; et al. (Frontiers in Tropical Diseases, 2025)
IntroductionGhana joined the Global Polio Eradication Initiative in 1996 to interrupt wild poliovirus transmission in the country. This was a collaborative effort by the Ghana Health Service (Disease Surveillance Department and the Expanded Program on Immunization) and the Polio Laboratory in the Noguchi Memorial Institute for Medical Research, University of Ghana.MethodsThe polio surveillance started from the southern regions and was extended to the northern regions over time. Surveillance officers were sensitized to improve case detection. The most important surveillance indicators—annualized non-polio AFP rate and stool adequacy—continued to improve, and the WHO targets for laboratory indicators of timeliness were met. The introduction of the oral polio vaccine in 1978 by the Expanded Program on Immunization led to a significant reduction in polio cases. The routine immunization coverage increased from 72% in 1999 to 94% in 2007, with an improvement in supplementary immunization activities.ResultsMolecular characterization of wild poliovirus from Ghana between 1995 and 2008 and vaccine-derived poliovirus from 2019 to 2022 revealed that the transmission of wild poliovirus and vaccine-derived poliovirus can be interrupted with active acute flaccid paralysis surveillance and adequate and efficient implementation of immunization activities. The country attained a polio- free status in 2015 after successfully submitting documentation to the Regional Certification Committee. Analysis of vaccine-derived polioviruses contributed to a better understanding of the poliovirus transmission, showing that the VDPV is indistinguishable from wild poliovirus and therefore poses a risk as a source of paralytic polio in a polio-free world.DiscussionGhana will sustain efforts to maintain polio- free status; intensify routine immunization to improve equity and OPV3 coverage; improve vaccine management and logistics; and enhance surveillance and outbreak preparedness, community engagement, and mobilization to eliminate the circulating vaccine-derived poliovirus. Furthermore, the country will strengthen partnerships with the WHO, UNICEF, CDC, Rotary International, and other stakeholders and secure dedicated funding to ensure consistent support for immunization and surveillance activities.